Characterization of significant molecular determinants of virulence of Enterovirus 71 sub-genotype B4 in Rhabdomyosarcoma cells - Yee, Isabel Pin Tsin *; Reham Ahmed Hashim Mohamed, *; Ong, Seng Kai *; Tan, Kuan Onn *; Poh, Chit Laa * (Elsevier, 2017)
One of the leading causes of the hand, foot and mouth disease (HFMD) is Enterovirus 71(EV-A71), displaying symptoms such as fever and ulcers in children but some strains can produce cardiopulmonary oedema which leads to death. There is no FDA-approved vaccine for prevention of severe HFMD. The molecular determinants of virulence for EV-A71 are unclear. It could be a single or a combination of amino acids that determines virulence in different EV-A71 genotype/sub-genotypes. Several EV-A71 strains bearing single nucleotide (nt) mutations were constructed and the contribution of each mutation to virulence was evaluated. The nt(s) that contributed to significant reduction in virulence in vitro were selected and each mutation was introduced separately into the genome to construct the multiply mutated EV-A71 strain (MMS) which carried six substitutions of nt(s) at the 5’-NTR (U700C), VP1-145 (E to G), VP1-98E, VP1-244K and G64R in the vaccine seed strain that had a partial deletion within the 5’-NTR region (nt. 475-485) of ∆11bp. In comparison to the wild type strain, the MMS showed low virulence as it produced very low RNA copy number, plaque count, VP1 and had 105-fold higher TCID50, indicative of a promising LAV candidate that should be further evaluated in vivo.